Analysis of the Impression of Using the TikTok Media firhan_ashari on the Motivation to Write Procedural Texts for Class VII Students - Setyowati, Dewi; Anas Ahmadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2024)
This research aims to describe students responses in using the tiktok firhan_ashari media as learning media on the motivation to write procedural texts for class VII students. This research was motivated by the fact that class VII students often play social media during learning activities, one of which is TikTok. This research uses qualitative research with a descriptive type. Data collection was carried out using documentation and questionnaire methods. The subjectct of this research were 28 class students at SMPN 36 Surabaya. The data collection instrument is a questionnaire sheet which is then analyzed using the Mean formula. The results of the research show that the implementation of learning using the TikTok firhan_ashari media has an effect on motivation to write procedural texts. The total percentage average score obtained from student responses was 86.424%, which is included in the very strong category. This shows that the use of the TikTok firhan_ashari media to motivate students to write procedural texts in class VII received a positive response and was able to provide motivation for students in writing procedural texts. Keywords: TikTok media, procedure text, writing ability, motivation